Pengaruh Digital Marketing Dan Potongan Harga Terhadap Keputusan Pembelian Pada Mahasiswa Program Studi Manajamen Fakultas Ekonomi Universitas Medan Area Di Platform Belanja Shopee - Anggeun Famelia; Wan Suryani; Eka Dewi Setia Tarigan (Universitas Medan Area, 2022)
The purpose of this study was to determine whether the role of digital marketing and price discounts had an effect on purchasing decisions for students of the Management study program, Faculty of Economics, Medan Area University. The research method used is quantitative survey research with primary data types in the form of questionnaires and multiple linear regression data analysis techniques. The results of this study indicate that partially digital marketing has a significant positive effect on purchasing decisions for students of the Management study program, Faculty of Economics, Medan Area University on the Shopee shopping platform. Partially, price discounts have a significant positive effect on purchasing decisions for students of the Management Study Program, Faculty of Economics, Medan Area University on the Shopee shopping platform. Simultaneously digital marketing and price discounts have a significant positive effect on purchasing decisions for students of the Management study program, Faculty of Economics, Medan Area University on the Shopee shopping platform.